FRI0288 TREATMENT PATTERNS AND PHARMACOUTILIZATION AMONG PATIENTS AFFECTED BY ANKYLOSING SPONDYLITIS: AN ITALIAN REAL-WORLD STUDY. (2nd June 2020) - Perrone, V.; Losi, S.; Filippi, E.; Antonelli, S.; Giovannitti, M.; Giacomini, E.; Sangiorgi, D.; Degli Esposti, L.
Abstract : Background: Ankylosing spondylitis (AS) is a chronic rheumatologic condition requiring lifelong treatments. To date, few real-world studies on AS patients in Italy are reported. Objectives: Aims of the study were to evaluate treatment patterns and to analyse pharmacoutilization on patients affected by AS in a real-world setting of Italian clinical practice. Methods: This observational study was based on administrative databases of a pool of Italian settings. A retrospective cross-sectional analysis was performed for years 2015-2017 to evaluate AS-diagnosed patients and, among them, to estimate percentage of treated and untreated ones. Patients were included if having a hospitalization discharge diagnosis at any level of AS (ICD-9-CM: 720.0) or exemption code for AS (054.720.0). Index date (ID) was date in which patients met one of the inclusion criteria. Patients with a prescription for drugs indicated for AS [non-steroidal anti-inflammatory drugs, disease-modifying antirheumatic drugs (DMARDs) - targeted synthetic (tsDMARDs) and biological (bDMARDs)] at ID were defined "treated". Patients without such drug prescriptions at ID were considered "untreated". To analyse treatment patterns of b/tsDMARDs-treated patients a longitudinal cohort study was conducted considering as inclusion periods the year 2014 and a period from 01/07/2016 to 30/06/2017. ID was date of first b/tsDMARDs prescription during inclusion period. Follow-up (F-up) lasted one year after ID. The interruption of treatment was defined as the absence of prescriptions in the last 3 months of F-up. Results: For cross-sectional-cohort: AS-diagnosed patients were 4, 824 in 2015, 5, 357 in 2016, 5, 894 in 2017. In all years analysed, about 50% of patients were male. Mean age±SD ranged from 51.5±13.7 (2015) to 52.4±14.0 (2017). Untreated patients were 33.6% (2015), 35.1% (2016) and 37.9% (2017), while patients in therapy with b/tsDMARDs were 22.7% (2015), 22.3% (2016) and22.2% (2017). The remaining percentage of patients were treated with csDMARDs/NSAIDS: 43.7% (2015), 42.6% (2016), 39.9% (2017)). In 2015 and 2016 all b/tsDMARDs-treated patients were in therapy with anti-TFN agents, while the advent of IL-inhibitors was observed starting from 2017 (8.2% b/tsDMARDs-treated patients with IL-inhibitors). For longitudinal-cohort: in 2014, 310 patients had a b/tsDMARDs prescription and during 1-year F-up 11.9% of them interrupted the treatment after a mean time ±SD of 83.3±66.9 days. Of the 183 patients who had a prescription of b/tsDMARDs at ID during 2016-2017, 22.4% had a treatment interruption after a mean time±SD of 134.4±86.1 days during F-up. Conclusion: This real-world study provided insights on AS treatment patterns. Preliminary results showed that approximately one third of AS patients are untreated and about one in five are treated with b/tsDMARDs. Despite the improvement in treatment duration observed from 2014 to 2016/17, still 22.4% of b/tsDMARDs-treated patients interrupted therapy in the most recent cohort. A larger sample size is needed to confirm results. Disclosure of Interests: Valentina Perrone: None declared, Serena Losi Shareholder of: minor stockholder at Eli Lilly, Employee of: Employed by Eli Lilly, Erica Filippi Shareholder of: minor stockholder at Eli Lilly, Employee of: Employed by Eli Lilly, Silvia Antonelli Shareholder of: minor stockholder at Eli Lilly, Employee of: Employed by Eli Lilly, Massimo Giovannitti Shareholder of: minor stockholder at Eli Lilly, Employee of: Employed by Eli Lilly, Elisa Giacomini: None declared, Diego Sangiorgi: None declared, Luca Degli Esposti: None declared